HUKUMAN MATI DALAM KITAB UNDANG-UNDANG HUKUM PIDANA DAN HUBUNGANNYA DENGAN HAK ASASI MANUSIA - Muhammad Ridwan Lubis (Universitas Islam Sumatera Utara, 2019)
Abstract Capital punishment is the toughest criminal punishment of all types of crimes; therefore, the threat of capital punishment is only directed at certain criminals. The offense threatened with capital punishment, is relatively smaller than the others. Such death penalty is a type of punishment that always causes pros and cons because it is considered contrary to human rights. Based on the above background, this journal discussion presents the relationship between the death penalty and human rights.The implementation of capital punishment is the most violent reaction to a crime because it does not provide an opportunity for the perpetrators to correct their behavior. On the other hand, the capital punishment is also a tool for fulfilling legal objectives, and it can also be a kind of shock therapy for other criminals or people who intend to commit crimes. The regulation of the death penalty in Indonesian criminal law as well as in other laws and regulations is still maintained because it is in accordance with the spirit of Pancasila and the 1945 Constitution of the Republic of Indonesia so that the death penalty is not contrary or violates human rights.